MANAJEMEN PEMBIAYAAN PENDIDIKAN MADRASAH ALIYAH SWASTA AR-RISALAH KRUENG SABEE ACEH JAYA - Sariakin, Sariakin; Faizah, Cut (LPPM Institut Pendidikan Nusantara Global, 2023)
The study is intended to see how education finance is regulated at MAS Ar-Risalah Krueng Sabee Aceh Jaya. This study is a case study. Information is obtained through observation, interviews, and information storage. Furthermore, so that the data can be trusted, several stages are carried out, namely the data source triangulation technique. The data analysis technique uses four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The implementation of education financing management includes the process of planning, using funds, monitoring and accountability. (2) Private Madrasahs cannot only depend on sources of funds from the government in fulfilling education funding. (3) Overall, the implementation of education financing management has been well implemented. The limitations in managing education financing at MAS Ar-Risalah Krueng Sabee Aceh Jaya include: (a) The management structure in financing management is still under the auspices of the foundation's management, school principals and treasurers so that there is no adequate supervision and accountability for financing management; (b) Contributions for educational development are determined collectively and adapted to the needs of students.